Curcumin Activates the Nrf2 Pathway and Induces Cellular Protection Against Oxidative Injury - Ashrafizadeh, Milad; Ahmadi, Zahra; Mohammadinejad, Reza; Farkhondeh, Tahereh; Samarghandian, Saeed (Current Molecular Medicine, 2020)
Curcumin is a naturally occurring polyphenol that is isolated from the rhizome of Curcuma longa (turmeric). This medicinal compound has different biological activities, including antioxidant, antibacterial, antineoplastic, and anti-inflammatory. It also has therapeutic effects on neurodegenerative disorders, renal disorders, and diabetes mellitus. Curcumin is safe and well-tolerated at high concentrations without inducing toxicity. It seems that curcumin is capable of targeting the Nrf2 signaling pathway in protecting the cells against oxidative damage. Besides, this strategy is advantageous in cancer therapy. Accumulating data demonstrates that curcumin applies four distinct ways to stimulate the Nrf2 signaling pathway, including inhibition of Keap1, affecting the upstream mediators of Nrf2, influencing the expression of Nrf2 and target genes, and finally, improving the nuclear translocation of Nrf2. In the present review, the effects of curcumin on the Nrf2 signaling pathway to exert its therapeutic and biological activities has been discussed.
Keywords: oxidative stress